(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Glaucoma is a potentially blinding disease,causing gradual loss of sight. It is often associated with increased intraocular pressure that can damage the optic nerve, which transmits images to the brain. Glaucoma can lead to permanent vision loss, if the damage continues. Without treatment, glaucoma can cause total permanent blindness within a few years. Glaucoma is one of the major causes of ocular morbidity and primary open–angle glaucoma is a major health problem. The prevalence of primary open- angle glaucoma (POAG) is estimated as being from 1.1-3% of western populations, over the age of 40 years, in both past and more recent population surveys. Objective: To evaluate and compare the value of Contrast sensitivity (CS) and automated perimetry among primary open-angle glaucoma (POAG) patients, glaucoma suspects and normal control. Materials and Methods: It was a prospective observational hospital based study conducted in National Institute of Ophthalmology & Hospital (NIO&H), Dhaka during the period from January 2006 to December 2006. A total of 30 POAG patients, 30 glaucoma suspects and 30 normal control subjects were recruited for the study. After complete baseline evaluation, all the study subjects underwent visual field assessment by Octopus automated field analyzer and CS evaluation by Low Contrast Flip Chart. Outcome measures were baseline CS of POAG patients, glaucoma suspects and normal controls, mean CS of POAG patients at 3 months after treatment, baseline MS of POAG patients, glaucoma suspects and normal controls in Octopus perimetry and retinal mean sensitivity (MS) of POAG patients 3 months after treatment. Results: Among the POAG patients MS was 22.23 dB, among glaucoma suspects MS was 27.50 dB and among normal controls mean MS was 30.0 dB; among the POAG patients mean CS was 2.99% whereas it was 2.20% and 1.41% respectively among glaucoma suspects and normal controls. Baseline CS had negative correlation with MS among POAG patients (correlation co-efficient, r = -0.908). It indicates that better CS is associated with higher MS. Out of 30 cases of POAG, 20 (66.67%) received medical and 10 (33.33%) received surgical treatment. Mean CS improves to 2.66% from baseline 2.99% after treatment and MS improves to 23.16 dB from base 22.23 dB after treatment. Correlation after three months of treatment was significantly negative (r = -0.86). Conclusion: As increased loss of MS of perimetry has been found to be associated with increased loss of CS, assessment of CS may become an easy, convenient tool for glaucoma diagnosis. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 90-92